An econometric approach between human development and poverty in North Eastern Region of India - Pradhan, Rudra P. (Information Management and Business Review, 2011)
An understanding the linkage between human development and poverty in general and economic development in particular is very imperative in emerging economies in the globe. The objective of this paper is to study the regional variation and causality between human development and poverty in the north-east India. The major finding of this paper is that there exists significant regional variation between human development and poverty in the north eastern states of India. While human development is substantially high in Mizoram and Manipur, it is low in other states. On the contrary, poverty is very low in Mizoram and Manipur, while it is considerably high in other states. The estimated results confirmed that human development (and its individual indicators) has a significant role to alleviate poverty in the north east India.